Self‐supporting Atmosphere‐Assisted Synthesis of 1D Mo2C‐based Catalyst for Efficient Hydrogen Evolution. Issue 38 (27th May 2021) - Chen, Mengying; Yang, Dongrui; Wu, Shifan; Zhou, Jiabei; Zhou, Dali; Liu, Can
Abstract: One‐dimensional materials exhibit fascinating properties in electrocatalytic applications but their fabrication faces the challenge of tedious and complicated operations. We have developed a bottom‐up strategy to construct a 1D metal carbide catalyst (Mo2 C@NC) consisting of ultrafine Mo2 C nanoparticles embedded within nitrogen‐doped carbon layers by simply calcining a mixture of ammonium molybdate, urea and melamine. Experimental results and thermodynamic calculations demonstrate that the retainable pyrolysis‐generated self‐supporting atmosphere plays a crucial role in the crystalline phase and morphology of materials. When functioned as an electrocatalyst for the hydrogen evolution reaction (HER), the achieved Mo2 C@NC presents an excellent catalytic activity as well as outstanding stability. This work could shed fresh light onto the facile synthesis of effective HER catalysts with 1D nanostructure. Abstract : A very fine catalyst : A 1D catalyst consisting of ultrafine Mo2 C nanoparticles and nitrogen‐doped carbon has been fabricated for the hydrogen evolution reaction. Self‐supporting gases play a vital role in building the 1D and porous structure of the materials, which facilitates charge and mass transfer during the catalytic process. The optimized catalyst exhibits a superior overpotential and Tafel slope.